2021
DOI: 10.1111/jcmm.16275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key candidate biomarkers for severe influenza infection by integrated bioinformatical analysis and initial clinical validation

Abstract: One of the key barriers for early identification and intervention of severe influenza cases is a lack of reliable immunologic indicators. In this study, we utilized differentially expressed genes screening incorporating weighted gene co‐expression network analysis in one eligible influenza GEO data set ( GSE111368 ) to identify hub genes associated with clinical severity. A total of 10 genes ( PBI , MMP8 , TCN1 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Fatty acid metabolism, α-linolenic acid metabolism and arachidonic acid metabolism inhibit the initiation and metastasis of cancer (Fig. 5 B) [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acid metabolism, α-linolenic acid metabolism and arachidonic acid metabolism inhibit the initiation and metastasis of cancer (Fig. 5 B) [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The genes expression within cell cycle module displayed obvious differences between moderate and severe influenza infection [ 4 ]. Since the cell cycle has been widely believed to be required for cellular homeostasis [ 17 ], changes of several critical transition points in cell cycle pathways could be a clear immune signature for disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Several viral, host and environmental factors impact disease severity leading to increased hospitalization and mortality [2]. Some studies identified that immune response, neutrophil function and cell cycle, as three distinct pathogenic mechanisms, were linked to disease progression of influenza infection [3][4][5]. T lymphocyte responses correlated with protection following influenza infection could be a sign to predict the disease severity [6].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is very promising to determine BPI in plasma as a marker of systemic inflammation and bacterial infection. Additionally, BPI is an endogenous inhibitor of angiogenesis by inducing apoptosis of vascular endothelial cells [19,20].…”
Section: педиатрияmentioning
confidence: 99%